2014
DOI: 10.1161/jaha.114.001152
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of the Risk Assessment Model of the International Medical Prevention Registry on Venous Thromboembolism (IMPROVE) for Medical Patients in a Tertiary Health System

Abstract: BackgroundHospitalized medical patients are at risk for venous thromboembolism (VTE). Universal application of pharmacological thromboprophylaxis has the potential to place a large number of patients at increased bleeding risk. In this study, we aimed to externally validate the International Medical Prevention Registry on Venous Thromboembolism (IMPROVE) VTE risk assessment model in a hospitalized general medical population.Methods and ResultsWe identified medical discharges that met the IMPROVE protocol. Case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
186
3
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(197 citation statements)
references
References 21 publications
5
186
3
3
Order By: Relevance
“…3 Notably, the investigators externally validated the IMPROVE associative risk assessment model in 2 additional databases, both of which showed accurate identification of patients at sufficiently low risk of VTE to omit thromboprophylaxis. 11,12 The primary objective of the current study was to compare the proportion of patients considered at high risk for VTE (and Can J Hosp Pharm. 2016;69(5):454-9 d'événements thromboemboliques chez les patients médicaux hospitalisés pourrait réduire l'utilisation de la thromboprophylaxie médicamenteuse, qui pourrait passer de 80 % à aussi peu que 7 %.…”
Section: Discussionmentioning
confidence: 99%
“…3 Notably, the investigators externally validated the IMPROVE associative risk assessment model in 2 additional databases, both of which showed accurate identification of patients at sufficiently low risk of VTE to omit thromboprophylaxis. 11,12 The primary objective of the current study was to compare the proportion of patients considered at high risk for VTE (and Can J Hosp Pharm. 2016;69(5):454-9 d'événements thromboemboliques chez les patients médicaux hospitalisés pourrait réduire l'utilisation de la thromboprophylaxie médicamenteuse, qui pourrait passer de 80 % à aussi peu que 7 %.…”
Section: Discussionmentioning
confidence: 99%
“…[1] While several risk assessment models exist for venous thromboembolism in medical patients, [2][3][4][5] published risk assessment models have limited generalizability and validation. [6] Although a few recent studies have validated existing risk assessment models, [5,7,8] these validation efforts lacked external validation, [5] have had limited external validation, [9] or have had largescale external validation with a risk assessment model that has limitations in predicting at-admission venous thromboembolism risk. [7,8] Additional largescale, external validation studies are important to help confirm or refute the accuracy of available risk assessment models, especially during hospital admission and based on detailed clinical data, as the performance of existing risk assessment models has been moderate at best in this setting.…”
Section: Introductionmentioning
confidence: 99%
“…Given that a patient's risk status may change during the course of hospitalization and especially to determine a patient's continued venous thromboembolism risk after hospital discharge, the original IMPROVE study also developed an associative model, including the additional risk factors of immobility, lower limb paralysis, and intensive care unit stay, which yielded an improved c-statistic of 0.69 [4]. Recent large-scale external validation studies of the associative IMPROVE risk assessment model have shown good calibration and discrimination, suggesting that the IMPROVE associative venous thromboembolism risk assessment model may reliably stratify venous thromboembolism risk,[7,8, 16] and this model has been incorporated into a recent large multicenter, multinational trial of post-hospital discharge thromboprophylaxis, the MARINER trial (ClinicalTrials.gov Identifier: NCT02111564). However, the main limitation of the IMPROVE associative risk assessment model is incomplete validation during hospital admission.…”
mentioning
confidence: 99%
“…It will evaluate postdischarge use of rivaroxaban 10 mg/day compared with placebo for 45 days in a selected group of patients at high risk for VTE. Eligible patients will have a D‐dimer concentration 2 or more times the ULN, plus elevated risk as demonstrated by a modified IMPROVE VTE risk score of 2 or 3, or with IMPROVE VTE risk scores of 4 or higher regardless of D‐dimer concentrations . The trial will enroll ~8000 patients; results are expected in May 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Current recommendations are limited to the acute inpatient period of care and do not support extending thromboprophylaxis beyond the period of immobilization or acute hospital stay. The IMPROVE VTE (International Medical Prevention Registry on Venous Thromboembolism) risk score is also widely used in clinical practice to identify medically ill patients at low and high risk for VTE within 90 days (Table ) . Patients with a score of 0–2 are considered to be at low risk; those with a score higher than 2 have a 9‐ to 23‐fold increased risk for developing VTE.…”
Section: Venous Thromboembolism Inpatient Risk Assessment Model Per Amentioning
confidence: 99%